"Green cannibalism" or an "organic inside job"? Empirical insights into the rivalry of ethical grocery types. Issue 6 (1st March 2019) - Frank, Phillip; Brock, Christian
Abstract: Despite having favorable purchase intentions toward organic groceries, the respective purchase behavior falls often short. This so‐called intention–behavior gap is investigated by exploring the impact of competing ethical products fulfilling green consumption motives ("green fit") as well or lacking credibility of organic groceries on organic purchase behavior. The first two studies ( n 1  = 225; n 2  = 321) assessing actual and reported purchase behavior are testing the impact of perceived substitutability of local and fair trade alternatives compared with organic groceries. A third study ( n 3  = 145) examines the impact of food miles and packaging on perceived product quality and credibility as possible reasons for a lacking "green fit" of organic groceries in terms of an experimental design. Local (fair trade) and organic groceries are perceived as substitute (complementary) alternatives. Additionally, local (organic) "green fit" impedes (enhances) the transformation from organic intentions into a respective purchase behavior. Wrapped organic produces with high food miles are linked to lower quality and credibility perceptions, reducing organic sales rates in favor of local groceries.